2000
DOI: 10.1080/02701367.2000.10608877
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Responsibility through Sport Education: Prospects of a Coalition

Abstract: The purpose of this study was to provide a database analysis of a combined sport model and from this to develop a theory from practice. In particular, the original concern was to examine the extent to which the teaching of personal and social responsibility (TPSR) could form a coalition with the Sport Education model. Forty-five 6th-grade boys, who had a previous history of struggling with the fair play requirements of Sport Education, participated in a 26-lesson season of Xball, an invasion game designed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0
21

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 6 publications
7
100
0
21
Order By: Relevance
“…One research prospective interests in the future may be the hybridization of models-based practice, in particular the hybridization of teaching for personal and social responsibility model with others, such as the cooperative learning (Fernández-Río, 2014) or the sport education model (Hastie & Buchanan, 2000;Menéndez & Fernández-Río, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One research prospective interests in the future may be the hybridization of models-based practice, in particular the hybridization of teaching for personal and social responsibility model with others, such as the cooperative learning (Fernández-Río, 2014) or the sport education model (Hastie & Buchanan, 2000;Menéndez & Fernández-Río, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The development of values has been principally studied in function of the accuracy of educational programs implementation (Catalano, Berglund, Ryan, Lonczak, & Hawkins, 2004;Danish & Nellen, 1997;Escartí, et al, 2003;Hastie & Buchanan, 2000;Hellison, 2011;Hodge & Danish, 1999;Martinek, McLaughlin & Schilling, 1999;McKenney & Dattilo, 2001), which although often use sport as a vehicle of values, they do not study its development according to the level of physical activity practice but the participation or not in the program.…”
Section: Jpes ®mentioning
confidence: 99%
“…Hastie and Buchanan (2000), in their work with middle school teachers using Sport Education in the USA, found that MBP encouraged, even required, a diversification in the teacher's role. Similarly, in their US study of one middle school teacher's use of Peer Teaching within a Sport Education unit, Wallhead and O'Sullivan (2007) suggested that such a pedagogical 'about-face' moved the teacher away from 'her' position as a provider of knowledge and instead gave her more opportunities to observe and assess her students' learning.…”
Section: Diversification In the Teacher's Rolementioning
confidence: 99%
“…Several comparative studies examine the effectiveness of the technical and tactical approach in relation to their impact on tactical knowledge and decision making, student motivation and engagement in the learning process, technique and technical knowledge acquisition as well as the level of physical activity (Alexander, Taggart, & Thorpe, 1996;Alison & Thorpe, 1997;Chatzipanteli & Digelidis, 2012;Clarke & Quill, 2003;Garcia & Ruiz, 2003;Graham, Ellis, Williams, Kwak, & Werner, 1996;Gray & Sproule, 2011;Hastie & Buchanan, 2000;Hastie & Curtner-Smith, 2006;Light, 2002;McCaughtry, Sofo, Rovegno, & Curtner-Smith, 2004;McNeill, Fry, Wright, Tan, & Schempp, 2004;Ormond, DeMarco, Smith, & Fischer, 1995;Pope & Grant, 1996;Turner, 1996a;Turner & Martinek, 1999). Recorded results indicate encouraging findings for the adoption of the tactical approach.…”
Section: Discussionmentioning
confidence: 99%